Between worlds : the rhetorical universe of Paradise lost - Pallister, Will, 1967- (University of Toronto Press, 2008)
William Pallister analyses the rhetorical methods that Milton uses throughout the poem and examines the effects of the three distinct rhetorical registers observed in each of the poem's major settings.